2016
DOI: 10.1186/s12883-016-0623-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with benign multiple sclerosis in the New York State MS Consortium (NYSMSC)

Abstract: BackgroundThis retrospective analysis explored prognostic factors associated with a benign multiple sclerosis (BMS) disease course at baseline and over the 4-year follow-up.MethodsPatients from the centralized New York State Multiple Sclerosis Consortium registry were classified as having BMS according to 3 different criteria centered on disease duration and disability. Additional analyses explored prognostic factors associated with BMS using the most conservative disability criteria (Expanded Disability Statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Our results support the assumption that subclinical inflammatory disease activity also occurs in seemingly benign and mild MS. So, there is justification for DMT use also in the benign course of the disease, regardless of the clinical relapse rate (Montalban et al., 2018 ; Ziemssen et al., 2016 ; Zivadinov et al., 2016 ). However, the evidence of the DMT effect on GM atrophy, especially in benign MS, is presently scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support the assumption that subclinical inflammatory disease activity also occurs in seemingly benign and mild MS. So, there is justification for DMT use also in the benign course of the disease, regardless of the clinical relapse rate (Montalban et al., 2018 ; Ziemssen et al., 2016 ; Zivadinov et al., 2016 ). However, the evidence of the DMT effect on GM atrophy, especially in benign MS, is presently scarce.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there are no established predictors for long‐term outcomes. It seems that a significant proportion of patients with benign MS develop cognitive decline, overall disability, and brain atrophy after a long follow‐up period (i.e., more than 20 years), even though there are no clinical relapses and neurological signs remain mild (Correale et al., 2012 ; Hirst et al., 2008 ; Mesaros et al., 2009 ; Portaccio et al., 2009 ; Rovaris et al., 2008 ; Zivadinov et al., 2016 ). The extent of brain atrophy in benign MS compared with an age‐matched healthy control group is scarcely investigated, reporting reduced subcortical and cortical GM in benign MS patients compared to healthy controls (Mesaros et al., 2008 ; Rovaris et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, benign MS was defined as having EDSS values below 2 and 3 separately for 10-year disease duration and 19.8% to 33.3% among 6258 patients were characterized as having benign MS. Positive prognostic factors at baseline included female sex and younger age at onset, and disease-modifying treatment and longer disease duration were found to be positive predictors at the end of 4 th year (9). In another study with long-term follow-up, the benign MS definitions of the previous study were used, female sex and the presence of fully recovering attacks with a low number of attacks indicated favorable outcome at the 20 th and 30 th years and 30 th year, respectively.…”
Section: Clinical Biomarkersmentioning
confidence: 91%
“…Risk factors include demographic and clinical characteristics, MRI activity, and other biomarkers. Natural history cohort studies have demonstrated that men with MS reach disability milestones faster and in larger numbers than women (12,13). However, other studies have found no association between sex and future disability (14).…”
Section: Prognostic Factorsmentioning
confidence: 99%